Double-swab 5% versus single-swab 10% iodophor for reducing methicillin-resistant Staphylococcus aureus with routine chlorhexidine bathing. (26th December 2022) - Heim, Lauren T.; Miller, Loren G.; Singh, Raveena D.; McKinnell, James A.; Catuna, Tabitha D.; Estevez, Marlene; Evans, Kaye D.; Tjoa, Tom K.; Gussin, Gabrielle M.; Dahl, Shaun D.; Budy, Linda; Peterson, Ellena M.; et al.
Abstract: In a prospective cohort study, we compared a 2-swabs-per-nostril 5% iodophor regimen with a 1-swab-per-nostril 10% iodophor regimen on methicillin-resistant Staphylococcus aureus carriage in nursing-home residents. Compared with baseline, both single-swab and double-swab regimens resulted in an identical 40% reduction in nasal carriage and 60% reduction in any carriage, skin or nasal.